The writ and health reform: Disillusionment of a dreamer judge [La tutela y reforma en salud: Desencanto de un juez soñador∗] (2013)
In the group of social, economic and cultural rights, the Colombian regulatory progress in health has been the most prominent in the world in recent decades. The Constitutional Court, bypassing the constitutional nature of these rights, recognized in some cases the provision of health as an individual right, protected as a fundamental right for writ instance. For the government and a sector of the doctrine, this has generated funding problems and disorder in the structure of the social security system, but for the other part of this doctrine is but a logical consequence of the new constitutionalism. Despite all these efforts and structural developments in jurisprudence, the state has failed to consolidate protection to ensure access and quality of health services, besides comprehensive protection jurisprudence remains fragile and uncertain.